Equity and impact: Ontario's infant rotavirus immunization program five years following implementation. A population-based cohort study. Issue 17 (17th April 2019) - Wilson, Sarah E; Rosella, Laura C; Wang, Jun; Renaud, Ariane; Le Saux, Nicole; Crowcroft, Natasha S; Desai, Shalini; Harris, Tara; Bolotin, Shelly; Gubbay, Jonathan; Deeks, Shelley L
Abstract: Background: Ontario implemented a publicly-funded rotavirus (RV) immunization program in 2011. Our objectives were to evaluate its impact on hospitalizations and emergency department (ED) visits for acute gastroenteritis (AGE) five years after implementation. Methods: We performed a population-based longitudinal retrospective cohort study to identify hospitalizations and ED visits for RV-AGE and overall AGE in all age groups using ICD-10 codes between August 1, 2005 and March 31, 2016. A negative binomial regression model that included the effect of time was used to calculate rates, rate ratios (RRs) and 95% confidence intervals (CIs) for AGE before and after the program's implementation, after adjusting for age, seasonality and secular trends. We examined the seasonality of RV-AGE hospitalizations among children under five before and after the program and explored its equity impact. Results: Following program implementation, RV-AGE hospitalizations and ED visits among children under five years declined by 76% (RR 0.24, 95% CI 0.20–0.28) and 68% (RR 0.32, 95% CI 0.21–0.50), respectively. In addition, hospitalizations and ED visits for overall AGE declined by 38% (RR 0.62, 95% CI 0.59–0.65) and 26% (RR 0.74, 95% CI 0.73–0.76), respectively, among children under age five. Significant reductions in both outcomes were also found across a range of age-strata. In the pre-program period, the mean monthly hospitalization rate for RV-AGE among children residing in the most marginalized neighbourhoods was 33% higher than those residing in the least marginalized (RR 1.33, 95% CI 1.17–1.52), this disparity was not evident in the program period (RR 0.95, 95% CI 0.69–1.32). We found no evidence of a seasonal shift in rotavirus pediatric hospitalizations. Interpretation: The introduction of routine infant rotavirus immunization has had a substantial population impact in Ontario. Our study confirms herd effects and suggests the program may have reduced previous inequities in the burden of pediatric rotavirus hospitalizations.